Barriers to Applying Knowledge Gained Through an Implementation Research Massive Open Online Course: An Explanatory Qualitative Study - Michael J. Penkunas PhD; Bella Ross PhD; Charlotte Pana Scott MS; Anna Thorson MD, PhD; Luis Fernando Baron PhD; Wafa Kammoun Rebai PhD; Hind Bouguerra MD; Pascal Launois MD, PhD (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
This study explores the barriers encountered by participants in applying knowledge gained from a massive open online course (MOOC) on implementation research (IR), particularly among learners in low- and middle-income countries (LMICs). Despite the rising demand for quality IR training, access remains limited in LMICs. The IR MOOC, created by the Special Program for Research and Training in Tropical Diseases, seeks to bridge this gap by providing free online IR training. Twenty-three interviews were conducted with participants from the French, Spanish, and English language sessions of the MOOC, and were analyzed using a general inductive approach. Barriers were identified at individual, organizational, community, and health authority levels. Individually, learners requested opportunities for deeper training and expert guidance. Organizational barriers included a lack of understanding and resistance to adopting IR methodologies. Community barriers involved limited roles and opportunities in IR and a lack of networking. Health authorities exhibited a lack of awareness and funding to support IR. Challenges in completing the course included language barriers, strict deadlines, limited internet connectivity, and a lack of localized case examples. This study highlights the importance of pairing online training with practical opportunities to apply newly learned skills. Our findings emphasize the need for expert guidance, improved language accessibility, and diverse case studies to support the development of a robust cadre of IR practitioners. Networking opportunities are crucial for connecting learners with IR practitioners and applying the knowledge acquired. Efforts to address these barriers could improve the effectiveness of IR training programs in LMICs.